2007
DOI: 10.1038/sj.ejcn.1602786
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency and anemia: disparity exists between children in American Samoa and children living within the US

Abstract: Background/Objectives: Healthy People 2010 emphasizes elimination of health disparity and improvements in anemia and iron deficiency (ID). The study purpose was to (1) determine the prevalence of anemia, ID and ID anemia (IDA) in children living in American Samoa and (2) compare the prevalence to that found in children living in the United States. Subjects/Methods: A total of 211 children from American Samoa, aged 1-5 years of age, participated in this cross-sectional study. Prevalence of anemia, ID and IDA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…The prevalence of anaemia in the current study is generally consistent with most prior studies in China, while lower than that in some low-income countries. Studies in Nepal and Kazakhstan reported significantly higher anaemia prevalence than did the present study (40 and 27 %, respectively) (25,26) , while studies in the USA and Colombia found results similar to the present study (27,28) . The present study found a mild prevalence of ID (6•2 %), but a significantly low prevalence of IDA (0•6 %), which is consistent with US studies (27) .…”
Section: Prevalence Of Anaemia/iron Deficiency/ Iron-deficiency Anaemiasupporting
confidence: 78%
“…The prevalence of anaemia in the current study is generally consistent with most prior studies in China, while lower than that in some low-income countries. Studies in Nepal and Kazakhstan reported significantly higher anaemia prevalence than did the present study (40 and 27 %, respectively) (25,26) , while studies in the USA and Colombia found results similar to the present study (27,28) . The present study found a mild prevalence of ID (6•2 %), but a significantly low prevalence of IDA (0•6 %), which is consistent with US studies (27) .…”
Section: Prevalence Of Anaemia/iron Deficiency/ Iron-deficiency Anaemiasupporting
confidence: 78%
“…In the Solomon Islands, 48 % of children aged 6–59 months are anaemic ( 28 ) , while more than half of children of the same age group are anaemic in Nauru ( 45 ) and Tuvalu ( 28 ) . In neighbouring American Samoa, the prevalence of anaemia is very similar in this age group: 33 % among those aged 1–4 years ( 46 ) . Also similar is the relationship between anaemia and age, with the odds of anaemia decreasing with age in both settings ( 46 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In neighbouring American Samoa, the prevalence of anaemia is very similar in this age group: 33 % among those aged 1–4 years ( 46 ) . Also similar is the relationship between anaemia and age, with the odds of anaemia decreasing with age in both settings ( 46 ) . The odds of any anaemia were nearly 120 % higher among children with an anaemic mother compared with those without, as expected based on the strong evidence linking maternal and child nutritional status ( 47 ) .…”
Section: Discussionmentioning
confidence: 99%
“…25 In 2008, the prevalence of anemia and IDA in American preschoolers was 9% and 2%, respectively. 26 It was estimated that ID and IDA in infants and toddlers in USA has decreased in the latter years. 27 In Canadian children aged 3-5 y, the prevalence of ID (by ferritin) was 3.2% and anemia 2.2%.…”
Section: Discussionmentioning
confidence: 99%